2021
DOI: 10.3390/antiox10091374
|View full text |Cite
|
Sign up to set email alerts
|

Connexin Gap Junctions and Hemichannels in Modulating Lens Redox Homeostasis and Oxidative Stress in Cataractogenesis

Abstract: The lens is continuously exposed to oxidative stress insults, such as ultraviolet radiation and other oxidative factors, during the aging process. The lens possesses powerful oxidative stress defense systems to maintain its redox homeostasis, one of which employs connexin channels. Connexins are a family of proteins that form: (1) Hemichannels that mediate the communication between the intracellular and extracellular environments, and (2) gap junction channels that mediate cell-cell communication between adjac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 151 publications
0
15
0
Order By: Relevance
“…An association between connexins, redox potential and oxidative stress is well established ( Quan et al, 2021 ; Zhang et al, 2021 ), although low or physiological levels NO could have a protective effect in lens epithelial cells ( Chamberlain et al, 2008 ). A high production of NO in human lens has been associated with cataracts, especially in hypertensive patients ( Ornek et al, 2003 ) and smokers ( Anitha et al, 2019 ), and a similar association has been found in animal models of hypertension and diabetes ( Abdul Nasir et al, 2017 ; Yadav et al, 2018 ).…”
Section: Cx46 Posttranslational Modifications and Their Potential Rel...mentioning
confidence: 99%
“…An association between connexins, redox potential and oxidative stress is well established ( Quan et al, 2021 ; Zhang et al, 2021 ), although low or physiological levels NO could have a protective effect in lens epithelial cells ( Chamberlain et al, 2008 ). A high production of NO in human lens has been associated with cataracts, especially in hypertensive patients ( Ornek et al, 2003 ) and smokers ( Anitha et al, 2019 ), and a similar association has been found in animal models of hypertension and diabetes ( Abdul Nasir et al, 2017 ; Yadav et al, 2018 ).…”
Section: Cx46 Posttranslational Modifications and Their Potential Rel...mentioning
confidence: 99%
“…The permeability and transport properties of these channels are implicated in lens epithelial growth and proliferation, Na + and water coupled transport, Ca 2+ transport, antioxidant gradients, and second messenger permeability ( Mathias et al, 2010 ; Slavi et al, 2014 ; Brink et al, 2020 ). One important nutrient that connexin channels circulate is the tripeptide glutathione (GSH), which is the main alleviator of oxidative stress in lens fiber cells ( Slavi et al, 2014 ; Braakhuis et al, 2019 ; Quan et al, 2021 ). The role of connexin channels in the lens has been primarily established using genetic knock-out (KO) and knock-in (KI) models ( Berthoud et al, 2014 ).…”
Section: The Lens Circulationmentioning
confidence: 99%
“…Age and oxidative stress in the lens are usually coincident and lead to changes in the lens proteome, including connexin channel density and regulation ( Gao et al, 2013 ; Gong et al, 2021 ; Quan et al, 2021 ). The lens is protected from oxidative damage by antioxidants, such as GSH, and chaperone proteins to prevent protein aggregation and dissolution from oxidative stress ( Giblin, 2000 ; Lim et al, 2020 ).…”
Section: Aging and Oxidative Stress Impact The Channels Underlying The Lens Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial evidence has shown that aggravated oxidative stress in the lens epithelial cells (LECs) layer is a vital initiation factor in cataract formation 5 . Previous studies have also indicated that exposure to environmental risk factors produces reactive oxygen species (ROS) which can disrupt the redox balance of LECs 6 resulting in oxidation of lens proteins, DNA damage and/or lipid peroxidation, all of which have been implicated in formation lens opacity 7…”
Section: Introductionmentioning
confidence: 99%